Vestibular rehabilitation training on balance among individuals with neck pain - Ipshita Adhikary; Drishti Pachauri; Lalit K Gupta; Supriya Awasthi (Oral Sphere Journal of Dental and Health Sciences, 2025)
Introduction: Vestibular function plays a crucial role in maintaining normal balance throughout day-to-day life. The neck muscles also play a role in maintaining the body's equilibrium. The study aims to assess the effect of vestibular rehabilitation on balance among the individuals with neck pain and to improve it through vestibular adaptive exercises. Through this study, individuals will be more aware and focused on balancing problems associated with neck pain while performing activities of daily living. Methodology: In total, 50 individuals who have neck pain will be participating in this study. Dynamic balance ability is evaluated by the time up and go (TUG) test and the star excursion balance test (SEBT). Static balance ability is tested using a one-leg stance test (OLST) and Romberg test. Baseline and one week post vestibular intervention will be collected. Result: The result shows that after conducting pre-test and post-test, there is an improvement among the individuals. The mean value for participants’ age is 20.8, and BMI =23.5. The SEBT (all directions) is significant at p-value≤ 0.05. Conclusion: By Vestibular Rehabilitation, Balance with neck pain and Vestibular function could be treated among individuals with neck pain.